Sexual Behaviour of Commercial Sex Workers; Islamic Perspectives and Health - Achyar Zein; Watni Marpaung (Universitas Islam Negeri Sumatera Utara, Medan, 2022)
Prostitution or Commercial Sex Worker (CSW) is exchanging money for sexual services. Someone who sells sexual services is referred to as a prostitute, although the term commercial sex worker is now more commonly used. Method: This study is a qualitative look at how prostitutes in Medan and Batam feel about God. When looking for information for a study on how prostitutes' religion affects their work and lives, it was found that there is not much to go on. To obtain this information, interviews were conducted. In these informal interviews, the participants may be unaware they are being interviewed systematically. The data collection strategy included in-depth interviews and observation of directly involved prostitutes. This method was used to determine how prostitutes thought about religious patterns and to improve and develop the theory. Results: Most Commercial Sex Workers (CSWs) in Medan, Indonesia, are generally unfamiliar with the actual meaning of religion. You can use